The Effect Of Green Accounting, Financial Performance And CSR On Firm Value With Firm Size As An Intervening Variable - Susana Dewi; Adi Dwi Purnomo; Hartono Hartono; Maesaroh Maesaroh; Diah Permata Sari (Nomico, 2024)
This research aims to determine: (1) The effect of green accounting on firm size, (2) The effect of financial performance on firm size, (3) The effect of CSR on firm size, (4) The effect of green accounting on firm value, (5) The effect of financial performance on firm value, (6) The effect of CSR on firm value, (7) ) The effect of firm size on firm value (8) The effect of firm size in mediating green accounting on firm value, (9) The effect of firm size in mediating financial performance on firm value, (10) The effect of firm size in mediating CSR on firm value. The sample for this research is coal sub-sector mining companies for the 2019-2022 period using the purposive sampling method. There are 9 companies that meet the criteria as research samples. The data analysis tool in this research uses SPSS version 26. The research results show that: (1) Green Accounting has no significant effect on Firm Size, (2) Financial Performance has no significant effect on Firm Size, (3) CSR has no significant effect on Firm Size, (4) Green Accounting has no significant effect on Firm Value, (5) Financial Performance has a significant effect on Firm Value, (6) CSR has no significant effect on Firm Value, (7) Firm Size has no significant effect on Firm Value, (8) Firm Size indirectly mediates the effect of Green Accounting on Firm Value, (9) Firm Size does not mediate the influence of Financial Performance on Firm Value, (10) Firm Size does not mediate the effect of CSR on Firm Value.